2011
DOI: 10.3390/molecules16010675
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adenosine Receptor Agonists in Regulation of Hematopoiesis

Abstract: The review summarizes data evaluating the role of adenosine receptor signaling in murine hematopoietic functions. The studies carried out utilized either non-selective activation of adenosine receptors induced by elevation of extracellular adenosine or by administration of synthetic adenosine analogs having various proportions of selectivity for a particular receptor. Numerous studies have described stimulatory effects of non-selective activation of adenosine receptors, manifested as enhancement of proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 63 publications
1
17
1
Order By: Relevance
“…We have shown that pharmacologically induced elevation of extracellular adenosine, i.e., nonselective activation of adenosine receptors, stimulates hematopoiesis in mice (e.g., [4][5][6], for review, see [7]). In a subsequent study using adenosine receptor agonists selective for individual receptor subtypes, it was revealed that activation of adenosine A 3 receptors by their selective agonist, N 6 -(3-iodobenzyl)adenosine-5′-N-methyluronadenosine (IB-MECA), stimulated proliferation of hematopoietic progenitor cells for granulocytes/macrophages (granulocyte/macrophage colony-forming cells (GM-CFC)) and erythrocytes (burst-forming unit erythroid (BFU-E)) [8].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that pharmacologically induced elevation of extracellular adenosine, i.e., nonselective activation of adenosine receptors, stimulates hematopoiesis in mice (e.g., [4][5][6], for review, see [7]). In a subsequent study using adenosine receptor agonists selective for individual receptor subtypes, it was revealed that activation of adenosine A 3 receptors by their selective agonist, N 6 -(3-iodobenzyl)adenosine-5′-N-methyluronadenosine (IB-MECA), stimulated proliferation of hematopoietic progenitor cells for granulocytes/macrophages (granulocyte/macrophage colony-forming cells (GM-CFC)) and erythrocytes (burst-forming unit erythroid (BFU-E)) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The system of adenosine receptors and their agonists has been shown to play a distinct regulatory role in the processes of cell proliferation and differentiation in normal, as well as suppressed hematopoiesis [for a review, see 8,9]. Numerous studies have revealed the significant role of the nonselective activation of adenosine receptors in stimulating hematopoiesis [e.g., [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Further experimentation, using agonists selected for the individual subtypes, has been aimed at finding out whether stimulation of one of the four subtypes is responsible for the previously observed hematopoiesis-stimulating and radioprotective effects. These experiments are described in detail in a separate review [ 161 ]. It follows from the findings that IB-MECA ( N 6 -(3-iodobenzyl)adenosine-5′- N -methyluronamide) stimulates the cycling of hematopoietic progenitor cells [ 162 ].…”
Section: Other Compounds Tested As Radioprotectors or Radiomitigatmentioning
confidence: 99%